Pengaruh Media Sosial Instagram @infogarut terhadap Pemenuhan Kebutuhan Informasi Pilkada Bagi Mahasiswa Universitas Garut : Studi Kuantitatif-Eksplanatif - Salma Nasya Ardhita; Achmad Wildan Kurniawan; Ismira Febrina (MUKASI: Jurnal Ilmu Komunikasi, 2025)
This study aims to analyze the impact of the Instagram account @infogarut in meeting the information needs of Garut University students regarding the Regional Head Elections, using a quantitative approach and the Uses and Gratification theoretical framework. A purposive sampling technique was used to select samples, namely followers of the Instagram account @infogarut who are active students at Garut University. Data collection was carried out by distributing questionnaires to respondents according to predetermined criteria using the Slovin formula. The results of the study indicate that students' needs for Regional Head Election information are positively and significantly influenced by the use of the Instagram social media account @infogarut. Statistically, Instagram @infogarut contributed 67.5% in meeting the information needs of Garut University students regarding the Regional Head Elections. These findings confirm that Instagram @infogarut plays an important role as an effective and relevant source of information in helping students meet the need for local political information in the democratic process, and is also closely related to the research objectives. This social media not only functions as a means of entertainment, but also as a political education platform that supports active student participation in regional head elections.